The Relationship between Body Appreciation Levels, Eating Attitudes and Physical Profiles of Turkish Elite Artistic Gymnasts - Pınar Tatlıbal (Journal of Educational Issues, 2024)
Body dissatisfaction and disordered eating behavior in athletes may occur when sports and social pressures require an ideal body standard, if the athlete perceives that his or her body does not conform to this ideal. For this reason, the aim of this study is to investigate the relationship between artistic gymnasts’ (AG) physical profiles, body appreciation levels and eating attitudes. A total of 32 elite AG (Turkish National Team), 13 women and 19 men, participated in this study. Height and body analyzes of the participants were measured. Body appreciation levels were determined by the Body Appreciation Scale (BAS), and eating attitudes were determined by the Eating Attitudes Test (EAT-26). With the Training Information Form, information about training frequencies and durations was provided. Comparative analyzes of the BAS and EAT-26 results of elite female and male gymnasts were performed. The physical profiles, eating attitudes and body appreciation levels of female AG were evaluated and the relationship between them was determined. While no significant correlation was found between the BAS, EAT-26 and physical profiles of the elite male AG, a negative significant correlation was found between the BAS and body mass index (BMI) of female elite AG (p < 0.05). It was concluded that while BMI rates of elite female AG increased, their body appreciation levels decreased. The BAS results of elite AG’ were found to be significantly higher than those of elite female AGs (p < 0.05).